The impact of disability-related deprivation on employment opportunity at the neighborhood level: does family socioeconomic status matter? - Ning Qiu; Yuxiao Jiang; Yuxiao Jiang; Zongyao Sun; Mengbing Du; Mengbing Du (Frontiers in Public Health, 2023)
IntroductionDifficulties in attaining employment significantly contribute to socioeconomic poverty among individuals with disabilities. However, our understanding of how socioeconomic deprivation experienced by individuals and families with disabilities influences employment opportunities remains incomplete. This study aims to explore the relationship between index of disability-related multiple deprivation (IDMD) and employment opportunities (EMPO), while also investigating the role of family socioeconomic status (FSES) in shaping this relation.MethodsThis study explores the heterogeneous effects of IDMD, FSES, and the interaction between IDMD*FSES on EMPO among four disabled population groups categorized by IDMD and FSES.ResultsResults reveal that IDMD has a significant negative impact on EMPO, suggesting that persons with disabilities are confronted with a poverty trap resulting from the relationship between IDMD and EMPO. Furthermore, FSES demonstrates an effective moderating role in the IDMD-EMPO relationship, with the greatest impact observed among disabled population groups characterized by high IDMD and low FSES.DiscussionThe findings suggest that family-level support is crucial for vulnerable groups of disabled individuals to overcome the poverty trap, surpassing the reliance on individual-level assistance alone. This study supports a paradigm shift in comprehending disability-related deprivation by acknowledging its association with families, thereby presenting opportunities to enhance the welfare of people with disabilities.